PELUANG BISNIS DIGITAL MELALUI AFFILIATE MARKETING DALAM PERSPEKTIF EKONOMI SYARIAH - Marianingsih, Ita; Zainullah, M. Ilham; Musyarrofah, Wildatun (Al-Idarah, 2025)
Affiliate marketing has emerged as a digital business model that offers significant opportunities to expand market reach and increase revenue through performance-based partnerships. In Indonesia, with the largest Muslim population, affiliate marketing, especially related to halal products, has great potential to grow, supporting the development of the digital economy and Islamic economy. The rapidly growing Islamic economy in Indonesia is driven by the need for a riba-free financial system and adaptive regulations, while affiliate marketing provides opportunities for small businesses and individual entrepreneurs to participate in the digital economy. However, significant challenges arise in maintaining brand integrity, preventing fraud, and ensuring alignment with Islamic economic principles, such as justice, transparency, and the prohibition of haram elements. This study uses a qualitative approach with a descriptive study to explore the implementation of affiliate marketing in the Islamic economy, focusing on how this model can be integrated with Islamic principles. Data is collected through semi-structured interviews with digital business practitioners and literature analysis related to Islamic economic principles and affiliate marketing. Data analysis is conducted using content analysis techniques to identify the alignment between affiliate marketing practices and Islamic principles. The results of this research are expected to provide insights into the application of business ethics in affiliate marketing strategies, as well as the importance of monitoring to ensure compliance with applicable regulations. This study also aims to demonstrate how affiliate marketing can contribute to the growth of a more just, transparent, and sustainable economy, while strengthening Indonesia's position in the global halal industry.